Gut health modulation through phytogenics in poultry: mechanisms, benefits, and applications - Oni, Aderanti Ifeoluwa; Oke, Oyegunle Emmanuel (Frontiers in Veterinary Science, 2025)
The potential of phytogenic feed additives (PFAs) to modulate gut health has drawn much attention as natural alternatives to antibiotics in poultry production. These plant-derived compounds, such as polyphenols, alkaloids, flavonoids, and essential oils exhibit various bioactive properties that improve gut microbiota composition, support immune function, and improve nutrient absorption by influencing gut morphology and digestive enzyme activity. Their antioxidant, anti-inflammatory, and antimicrobial properties help maintain and improve overall poultry performance and lower the prevalence of diseases related to gut and intestinal integrity. By promoting a balanced gut microbiota, phytogenics help reduce enteric infections, promote beneficial bacteria, and suppress pathogenic microbes, reducing the need for antibiotic growth promoters. PFAs are valuable tools for sustainable poultry production since they have been connected to enhanced feed conversion efficiency, growth performance, and meat quality in addition to their health benefits. However, further research and standardization are needed to address issues, including regulatory compliance, appropriate dosage determination, and variability in the composition of bioactive compounds. To improve their stability and effectiveness, future research should improve PFA formulations, examine their synergistic interactions with other feed additives, and create innovative delivery systems such as microencapsulation. A promising strategy for enhancing animal welfare, lessening the impact on the environment, and guaranteeing antibiotic-free poultry production is the incorporation of phytogenics into poultry feed. Phytogenics can play a significant role in the future of sustainable poultry farming by tackling the current issues and maximizing their uses.